2020 – The Lecturer at a Crossroads of Teaching and Learning in Academia in Israel - Davidovitch, Nitza; Wadmany, Rivka (Journal of Education and e-Learning Research, 2021)
The COVID-19 pandemic has created the greatest known disruption to the education system in Israel and in many countries around the globe, resulting in decisions to switch to online learning in all subjects. In the current study we examined lecturers’ opinions on the advantages and disadvantages of online teaching from various aspects, from a systemic, multi-institutional perspective. The findings indicate that only about a third of the lecturers expressed a preference for online learning. The lecturers mentioned the lack of social and emotional interactions (SEL) between students and lecturers as one of the main disadvantages of online learning. In addition, most of the lecturers do not consider online learning as providing an advantage in the quality of teaching and learning. The study also indicates the need for perceptual changes among lecturers, so that they will reexamine the teaching and learning processes and adapt their role and responsibilities to the new opportunities enabled by today’s technological tools and learning environments. The findings also indicate that the success of online learning requires appropriate pedagogical educational approaches rather than replication of traditional frontal teaching patterns on digital platforms. The findings call for in-depth discussion among higher education policymakers and academic institutions on the new and effective purpose of the campus in the post-covid period, the distinction between the virtual and the real in academic instruction, and the challenges and ways of coping with the new reality.